Developing a National Trauma Research Action Plan: Results from the geriatric research gap Delphi survey. Issue 2 (8th August 2022) - Joseph, Bellal; Saljuqi, Abdul Tawab; Phuong, Jimmy; Shipper, Edward; Braverman, Maxwell A.; Bixby, Pamela J.; Price, Michelle A.; Barraco, Robert D.; Cooper, Zara; Jarman, Molly; Lack, William; Lueckel, Stephanie; et al.
Abstract : The National Trauma Research Action Plan (NTRAP) Geriatric Trauma Panel comprising interdisciplinary experts identified gaps in the geriatric trauma literature, generated research questions, and prioritized those them using a consensus-driven Delphi survey approach. #NatTrauma. Abstract : BACKGROUND: Treating older trauma patients requires a focus on the confluence of age-related physiological changes and the impact of the injury itself. Therefore, the primary way to improve the care of geriatric trauma patients is through the development of universal, systematic multidisciplinary research. To achieve this, the Coalition for National Trauma Research has developed the National Trauma Research Action Plan that has generated a comprehensive research agenda spanning the continuum of geriatric trauma care from prehospital to rehabilitation. METHODS: Experts in geriatric trauma care and research were recruited to identify current gaps in clinical geriatric research, generate research questions, and establish the priority of these questions using a consensus-driven Delphi survey approach. Participants were identified using established Delphi recruitment guidelines ensuring heterogeneity and generalizability. On subsequent surveys, participants were asked to rank the priority of each research question on a nine-point Likert scale, categorized to represent low-, medium-, and high-priority items. The consensus was defined as more than 60% of panelists agreeing on the priority category. RESULTS: A total of 24 subject matter experts generated questions in 109 key topic areas. After editing for duplication, 514 questions were included in the priority ranking. By round 3, 362 questions (70%) reached 60% consensus. Of these, 161 (44%) were high, 198 (55%) medium, and 3 (1%) low priority. CONCLUSION: Among the questions prioritized as high priority, questions related to three types of injuries (i.e., rib fracture, traumatic brain injury, and lower extremity injury) occurred with the greatest frequency. Among the 25 highest priority questions, the key topics with the highest frequency were pain management, frailty, and anticoagulation-related interventions. The most common types of research proposed were interventional clinical trials and comparative effectiveness studies, outcome research, and health care systems research. Abstract :